Characterization of spontaneous phage-resistant derivatives of Lactobacillus delbrueckii commercial strains - Guglielmotti, Daniela Marta (2006)
A total of 44 spontaneous phage-resistant mutants were isolated from three commercial Lactobacillus delbrueckii strains by secondary culture and agar plate methods. Phenotypic characteristics related to their phage-resistance capacities, i.e. plaquing efficiency, phage-resistance stability, lysogeny and adsorption rates were determined. The morphological,  biochemical (sugar fermentation patterns) and technological (acidifying and proteolytic activities and acidification kinetics) properties of mutants were also studied. Amplification and restriction analysis of the 16S rRNA gene (PCR-ARDRA) was applied to confirm strain identity at the subspecies level. Random amplification of polymorphic DNA (RAPD-PCR) was used to determine genetic diversity among the isolates and their respective parent strains. The secondary culture method was the most useful for obtaining phage-resistant mutants. Phage resistance stability was a variable property among the isolates, but a high level of resistance was exhibited as quantified by the efficiency of plaquing. Furthermore, a total absence of spontaneous lysogeny was demonstrated. Adsorption rates were heterogeneously distributed among the three groups of mutants. All mutants isolated from two sensitive strains were similar to them with respect to technological properties. Two groups of mutants with distinctive technological properties were isolated from the other sensitive strain. PCR-ARDRA revealed that two out of three sensitive strains identified commercially as Lb. delbrueckii subsp. bulgaricus were actually Lb. delbrueckii subsp. lactis. Some of the phage-resistant mutants that were obtained might be used in culture rotation programs without regulatory restrictions when commercial strains become sensitive to phages present in industrial environments.